Accumulation of Amikacin in Synovial Fluid After Regional Limb Perfusion of Amikacin Sulfate Alone and in Combination With Ticarcillin/Clavulanate in Horses. Issue 3 (27th January 2014) - Zantingh, Alanna J.; Schwark, Wayne S.; Fubini, Susan L.; Watts, Ashlee E.
<x xml:space="preserve">Abstract</x> Objectives To determine the effect of regional limb perfusion (RLP) with amikacin sulfate alone and in combination with ticarcillin/clavulanate on synovial fluid concentration and antimicrobial activity of amikacin. Sample Population Experimental study. Methods RLP with amikacin alone (A; 2.5 g) or amikacin and ticarcillin/clavulanate (AT; 2.5 g amikacin, 7 g ticarcillin/clavulanate) was performed with a tourniquet placed at mid‐antebrachium in standing, sedated horses. Perfusate blood was collected immediately after injection and again before tourniquet release. Blood from the jugular vein was collected before tourniquet release. Synovial fluid from the middle carpal joint was collected 0, 30, and 60 minutes after tourniquet release. Amikacin concentration and antimicrobial activity of synovial fluid against Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa were determined. Results There was significantly lower amikacin concentration in the middle carpal joint synovial fluid of group AT compared with group A at 30 minutes (AT = median 4.4 µg/mL, IQR 3.0–11.2 µg/mL; A = 17.5 µg/mL, 6.6–80.1 µg/mL) and 60 minutes (AT = median 4.6 µg/mL, IQR 3.1–8.1 µg/mL; A = 15.0 µg/mL, 6.7–61.7 µg/mL) after tourniquet release. Zones of inhibition for ticarcillin‐resistant Klebsiella pneumoniae from group AT were significantly smaller than group A from synovial fluid at 30 and 60 minutes after tourniquet release and in the perfusate serum before tourniquet release. Conclusions The combination of amikacin with ticarcillin/clavulanate during RLP resulted in significantly lower amikacin synovial concentration and antimicrobial activity on amikacin susceptible and ticarcillin resistant cultures compared with amikacin alone.